Peacebuilding fragility and the dynamics of implementation: The Disarmament, Demobilisation and Reintegration process during ONUMOZ in Mozambique - Bennett, Monique Jessica (Stellenbosch : Stellenbosch University, 2026)
Thesis (DPhil)--Stellenbosch University, 2026.